Water‐Triggered Spontaneously Solidified Adhesive: From Instant and Strong Underwater Adhesion to In Situ Signal Transmission (Adv. Funct. Mater. 44/2022). (28th October 2022) - Zheng, Si Yu; Zhou, Jiahui; Wang, Shuaibing; Wang, Yan‐Jie; Liu, Shanqiu; Du, Guangyan; Zhang, Dong; Fu, Jimin; Lin, Ji; Wu, Zi Liang; Zheng, Qiang; Yang, Jintao
Abstract : Underwater Adhesives In article number 2205597, Si Yu Zheng, Jimin Fu, Jintao Yang, and co‐workers design a polymeric glue based on triazole‐beared macromolecules and ionic liquids, which can flow freely to fill the crack with various morphology and solidify rapidly to achieve fast, robust, long‐lasting adhesion under seawater. Furthermore, the glue possesses additional functions of underwater sensing and fluorescent labeling, which exhibits great potentials in underwater repair and follow‐up crack monitoring.